Pembolehubah-Pembolehubah Bukan Akademik dan Pencapaian - Ng , Wai Kong (Penerbit Universiti Sains Malaysia, 1985)
Article attempts to identify some non-traditional variables that may determine achievement in a University - level course. 141 students' responses were analysed and their achievements were com: pared with their individual scores or ranking with regards "learning style", "seating", "evaluation of course", "number of friends", "perception of university environment" and "sex" . It was proposed that apart from the usual ability scores, such non-traditional variables may influence achievement. Amongst these variables, "learning style", "perception of university environment", "sex" and "number of friends" were shown to have significant influences on achievement. University education should therefore be cognisant of such variables in their conduct of classes and in student.advisory functions .